Analisis Hukum Kekerasan Seksual oleh Tenaga Pendidik terhadap Murid: (Studi Putusan Mahkamah Agung No. 5642 K/PID.SUS/2022) (Deposisi: Jurnal Publikasi Ilmu Hukum, 2025)
This journal analyzes sexual violence by educators against students by analyzing Supreme Court Decision No. 5642 K/Pid.Sus/2022 using normative legal research methods. The primary focus of this research is the abuse of power relations by perpetrators holding positions of authority, as well as the legal protections afforded to child victims. Furthermore, this paper compares the provisions on sexual violence in the Child Protection Law and the Sexual Violence Criminal Law (UU TPKS). The findings indicate that courts impose harsher sentences on perpetrators who abuse their trust as educators and place victims at the center of the legal process, ensuring guarantees of recovery, psychological rehabilitation, restitution, and the right to education. The judges' approach in the ruling also reflects the spirit and principles of victim protection as outlined in the TPKS Law, including recognition of power dynamics, psychological pressure, and the importance of a victim-centered perspective. The TPKS Law expands the scope of sexual violence beyond physical aspects to include psychological and structural dimensions, which were previously not clearly regulated in other laws.  Therefore, this paper emphasizes the importance of harmonizing the two laws to create a more just, progressive, and victim-centered legal system, especially for children in educational settings. This research is expected to contribute to strengthening a more comprehensive and child-oriented legal approach.